(untitled) (Economics and region, 2023)
After the end of the 30-year period of occupation, the restoration and rebuilding of the liberated lands has become one of the most important and urgent problems facing the country. In the post-occupation period, that is, in the last two years, important steps have been taken by the Azerbaijani state in the development of Karabakh. Great work has been done in the direction of ensuring security, infrastructure construction, agriculture and tourism. The projects implemented, in progress and planned to be implemented in the future in the liberated lands will have a significant impact on the development of tourism in the Karabakh region. It should be noted that the correct assessment of the potential of these areas, their future development and, most importantly, the development of tourism will make a significant contribution to the restructuring and development of Karabakh, as well as to the development of the Azerbaijani economy towards the non-oil sector. Karabakh region is a region with rich tourism potential. Here there are opportunities for the establishment and development of various types of tourism. Simply, the destruction of these lands by Armenians and the destruction of infrastructure during the occupation are rapidly slowing down the development of tourism in Karabakh. The total reconstruction value of the liberated Karabakh region is measured in billions. It is not possible to carry out these works and to revive Karabakh and to carry out these works quickly at the expense of the country’s economy. It should be noted that last year, 4,4 billion manats were allocated from the state budget for the implementation of the work in Karabakh. However, the estimated appropriation for the complete restructuring of Karabakh is more than 50 billion manats. Therefore, ensuring and increasing the investment flow to this region is one of the other urgent issues. In Karabakh, which has the opportunity to develop at the world level in the next 10-15 years with its own tourism potential, it is very important to research and apply the world tourism management in terms of methodology in order to benefit from these opportunities of the tourism sector. If the experiences of many developed countries in this field are applied correctly and in a planned manner in Karabakh, the region will become one of the leading regions of the world tourism sector.